Penyuluhan Hukum sebagai Upaya Membentuk Kecerdasan Pemilih Pemula pada Pemilu 2024 - Dadi, Agustinus F Paskalino; Bhute, Lasarus Didimus; Gobang, Paulus Devian Asno (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
General elections (elections) have an important meaning in the implementation of democracy. Elections are a means of implementing people's sovereignty. Therefore, it is hoped that the election will be democratic and participated in by all members of the community who have met the requirements. One group of people who need serious attention is the group of first-time voters. Beginner voters as participants who have never participated in an election before are expected to participate in the 2024 election intelligently. This means that beginner voters are expected to understand election rules, get to know election participants, know about voting mechanisms, and matters related to hoaxes and money politics. Good understanding and adequate knowledge can make beginner voters to participate in elections well, avoid election violations, and can choose candidates based on good criteria. This situation and condition are also experienced by students at Wonda Restoration Vocational School. There are 82 Restoration Vocational School students in the category of beginner voters who need to broaden their horizons and knowledge about elections. Various election regulations and their changes need to be studied and explored through legal education activities. Through socialization about election law, it is hoped that students can become intelligent voters during the elections at 2024.